Donor Cell Myeloid Sarcoma in an Umbilical Cord Transplant Patient: A Case Report and a Review of the Literature - Hayes, Christi; Petersen, Bruce; Malone, Adriana (Case Reports in Hematology, 2015)
Donor cell leukemia (DCL) represents a rare complication of allogeneic transplantation. The precise incidence remains unclear, though it may be higher following umbilical cord blood transplants. Here, we present an unusual case of a patient with B-ALL who presented with a donor derived myeloid sarcoma of the heart following a double cord blood transplant. To our knowledge, it is the first case of sarcomatous or chloromatous presentation of DCL following a UCBT.